A comparison of different established and novel methods to determine horses' laterality and their relation to rein tension - Kuhnke, Sandra; König von Borstel, Uta (Frontiers in Veterinary Science, 2022)
The aim of the present study was to assess agreement between established and novel methods to determine laterality and to identify the distribution of laterality in warmbloods and Thoroughbreds. Nine different methods to investigate horse’s laterality outside a riding context and during riding were compared across two groups of horses (sample A: 67 warmblood- type horses, sample B: 61 Thoroughbreds). Agreement between any two methods was assessed with Mc Nemar’s test or Bowker’s Test of Symmetry and deviation from equal distributions were assessed with chi²-tests. Continuous variables such as rein tension parameters were analyzed using ANOVA or linear mixed models. Generally, laterality test results obtained outside a riding context did not agree with laterality during riding or among each other (Bonferroni corrected p>0.0018). However, the rider’s assessment of her/his horse’s laterality allowed conclusions on rein tension symmetry (p=0.003), and it also agreed substantially with the lateral displacement of the hindquarters (p=0.0003), a method that was newly developed in the present study. The majority of warmbloods had their hindquarters displaced to the right (73.1%, Χ²=14.3; p<0.0001). The pattern of lateral displacement of the hindquarters was similar in the Thoroughbred sample (right: 60.7%, left: 39.3%), but did not deviate significantly from an equal distribution (Χ²=2.8; p>0.05). Laterality seems to be manifested in different ways, which generally are not related to each other. Attention should be paid to the desired information when selecting methods for assessment of laterality. Horse’s laterality has an impact on the magnitude and symmetry of rein tension. Matching horses and riders according to their laterality might be beneficial for the stability of rein tension and thus improve training.